How Can West African Rice Compete in Urban Markets? A Demand Perspective for Policymakers - Fiamohe, R.; Demont, M.; Saito, Kazuki; Roy-Macauley, Harold; Tollens, E. (Wiley, 2018)
In West Africa, rice produced locally falls short of meeting the demand and preferences of urban consumers. We analyzed the challenges facing local rice in urban markets and identified policies that can be implemented to improve the competitiveness of the regional rice sector. We argue that without addressing the demand side of the value chain, efforts on the supply side might fall short in reducing import dependency. Evidence suggests that while imported rice has easy access to urban markets, local rice faces more challenges in reaching urban consumers. The low market share of local rice in urban markets is in part due to consumers' dislike of local rice as it is perceived as being of inferior quality relative to imported rice. Local rice also tends to fetch lower prices. The experimental studies reviewed suggest, however, that urban consumers are willing to pay price premiums for local rice if its quality is upgraded. We propose a two‐stage policy sequence: (i) encouraging investment in quality upgrading; (ii) gradually increasing the Common External Tariff (CET) from 10 to 35 per cent to increase cost‐competitiveness of West African rice relative to imported rice. To stabilise and finance the sector, we further advocate the establishment of a flat‐rate levy on the value of rice imports.